2009
DOI: 10.1007/s11427-009-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials in a Go/Nogo task of abnormal response inhibition in heroin addicts

Abstract: Inhibitory control dysfunction is regarded as a core feature in addicts. The major objective of this study was to explore the time course of response inhibition in chronic heroin addicts and provide the neurophysiological evidence of their inhibitory control dysfunction. The amplitudes and latencies of ERP components were studied in fourteen heroin addicts (mean duration of heroin use being (13.54+/-5.71) years (Mean+/-SD), average abstinence being ((4.67+/-6.44) months)) and fourteen matched healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 48 publications
(68 reference statements)
3
53
2
1
Order By: Relevance
“…92 It should be noted, however, that inhibitory requirements in this task were low given the high probability of no-go trials (i.e., 50% of the trials were no-go trials), so that the task may have been too easy to reveal differences in inhibitory control between those with opiate dependence and controls.…”
Section: Inhibitory Control In Individuals With Opiate Dependencementioning
confidence: 96%
“…92 It should be noted, however, that inhibitory requirements in this task were low given the high probability of no-go trials (i.e., 50% of the trials were no-go trials), so that the task may have been too easy to reveal differences in inhibitory control between those with opiate dependence and controls.…”
Section: Inhibitory Control In Individuals With Opiate Dependencementioning
confidence: 96%
“…More studies have been conducted in participants with a mean age greater than 40 years in the area of prepotent response inhibition, although there is scarcity in research in samples older than age of 50. In these studies, a significant association has been shown between performance in the prepotent response inhibition tasks and cocaine (Parvaz et al, 2012; Hester et al, 2007) and alcohol dependence (Sjoerds et al, 2014; Thoma et al, 2007; Lawrence et al, 2009; Goudriaan et al, 2006), and no significant effects have been found for heroin use (Liang et al, 2014; Yang et al, 2009). Research in older samples exists to a very limited extent, warranting future research about how impulsive behavior changes with normal aging and its effects on drug use.…”
Section: Little Focus After Middle Adulthood: “Maturing-out” Phenomentioning
confidence: 99%
“…Based on our findings, in addition to capturing attention, drug-related cues can disrupt mechanisms of response inhibition even though a longer period of abstinence, which expanded upon general inhibition function deficits associated with heroin use (Yang et al, 2009;Yuan et al, 2009). Our findings highlight the importance of assessing and improving the ability of inhibiting drug-related cue reactivity in heroin abstainers.…”
Section: Discussionmentioning
confidence: 68%
“…Evidence suggests that deficits in inhibitory functions associated with heroin use could remain even months after abstinence (Fu et al, 2008;Yang et al, 2009;Yang et al, 2015b;Yuan et al, 2009) and contribute to substance use initiation and escalation (Mahmood et al, 2013;Nigg et al, 2006). From a clinical point of view, being able to inhibit drug seeking and intake when exposed to drug-related cues is very important for heroin abstainers to maintain abstinence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation